Specific Heat Capacity Measurements of Selected Meteorites for Planetary Surface Temperature Modeling. Issue 11 (19th November 2021) - Piqueux, Sylvain; Vu, Tuan H.; Bapst, Jonathan; Garvie, Laurence A. J.; Choukroun, Mathieu; Edwards, Christopher S.
Abstract: Specific heat capacity Cp(T) is an intrinsic regolith property controlling planetary surface temperatures along with the albedo, density, and thermal conductivity. Cp(T) depends on material composition and temperature. Generally, modelers assume a fixed specific heat capacity value, or a standard temperature dependence derived from lunar basalts, mainly because of limited composition‐specific data at low temperatures relevant to planetary surfaces. In addition, Cp(T) only appears to vary by a small factor across various materials, in contrast with the bulk regolith thermal conductivity, which ranges over ∼3–4 orders of magnitude as a function of the regolith physical state (grain size, cementation, sintering, etc.). For these reasons, the impact of the basaltic assumption on modeled surface temperature is often considered unimportant although this assumption is not particularly well constrained. In this paper, we present specific heat capacity measurements and parameterizations from ∼90 to ∼290 K of 28 meteorites including those possibly originating from Mars and Vesta, and covering a wide range of planetary surface compositions. Planetary surface temperatures calculated using composition‐specific Cp(T) are within ± 2 K of model runs assuming a basaltic composition. This ± 2 K range approaches or exceeds typical instrumental noise or other sources of modeling uncertainties. These results suggest that a basaltic assumption for Cp(T) is generally adequate for the thermal characterization of a wide range of planetary surfaces, but possibly inadequate when looking at leveraging subtle trends to constrain subsurface layering, roughness, or seasonal/diurnal volatile transfer. Plain Language Summary: Specific heat capacity describes how much energy is required to increase the temperature of a given mass of material by 1 K. Specific heat capacity depends on the composition of the material and its temperature, and this is one of the parameters needed by modelers to calculate planetary surface temperatures. However, few specific heat capacity measurements have been acquired for planetary materials below room temperature, and modelers generally assume basaltic specific heat capacity trends or even a fixed value. Here we address this knowledge gap by presenting laboratory‐specific heat capacity measurements from ∼90 K to room temperature of 28 meteorites covering a wide range of surface compositions, including samples potentially from Mars and Vesta and various types of Solar System asteroidal bodies. The impact of using composition‐specific heat capacity compared to a standard lunar basalt is variable, but generally limited to a couple of Kelvin at most, which is typically not important when deriving the physical properties of a surface layer (e.g., grain size, cementation, density, etc.). However, such unbudgeted error can become significant when estimating uncertainties, or when seeking the subtle signature of heterogeneity (layering, roughness, etc.). Key Points: Specific heat capacity Cp(T) measurements and parameterizations are provided for 28 meteorites from ∼90 to ∼290 K Planetary surface thermal modelers often treat Cp(T) as composition‐independent, but it can vary by ∼70% as a function of composition The impact of composition‐specific Cp(T) on modeled surface temperatures is modest, but not always inconsequential